Examining Psychological Elements in the Works of Khaled Hosseini - Shaghayegh Tamizifar; Mohammad Ebrahim Irajpour; Zahra Aghababaii (Literary Arts)
Khaled Hosseini, the acclaimed Afghan-American novelist, is renowned for his poignant narratives that delve beyond mere storytelling into the complexities of psychology and sociology. His novels, which resonate with diverse audiences, are celebrated for their rich character development and strong themes, capturing the attention of literature enthusiasts. These works skillfully speak across generations, unveiling the intricacies of familial bonds, secrets, and legacies, appealing to readers captivated by multi-generational tales and the dynamics of complex characters. Moreover, Hosseini's works offer profound insights into the culture, history, and social norms of Afghanistan. By evoking emotions ranging from the anguish of betrayal to the joy of connection, his writing fosters empathy for the characters, setting his prose apart from other literary works. The masterful intertwining of psychological themes with cultural authenticity solidifies his standing as a distinguished literary figure. This study aims to dissect various aspects of Hosseini's work with a focus on analyzing psychological elements. It seeks a deeper understanding of the intricate relationship between literature, psychology, and sociology depicted in Hosseini's prominent works, highlighting literature's power to touch the human heart and soul.